JC polyomavirus (JCV, HPyV2) seropositivity prevalence in healthy subjects: Systematic review and meta-analysis - Lenka J. Kimla; David Segal (PLoS ONE, 2026)
Background JC polyomavirus (JCV, HPyV2) causes progressive multifocal leukoencephalopathy and has been linked to cancer development. JCV may naturally be highly prevalent in the human population and not just in diseased populations. Objective The aim of this study was to the estimate the overall seroprevalence of JCV in the healthy human population by age of subjects, region or country of study, and assay methodology. Methods A systematic review and meta-analysis with meta-regression using STATA 18. Results Pooled JCV seroprevalence from 25 population-level studies (N = 18,331) was 61% (95% CI, 56% − 66%, z = 33.84, p < 0.001). Meta-regression and subgroup analyses showed that subject age was the only predictive variable on JCV seroprevalence ( z = 2.93, p = 0.003). Age was not normally distributed across seroprevalence. A detrended normal P-P plot under the cubic model with age on seroprevalence explained 99.9% of variance in the dataset (R 2 = 0.999). The theories that grounded this study were the ecological systems theory, which support the study result that JCV infection appears ubiquitous in the human population and may be acquired early in life by two years of age. Conclusion JCV seroprevalence starts high in early infant age, descends in late childhood/early adulthood, and starts to rise again towards older age, most probably, by viral reactivation due to immune senescence. The overall findings support the hypothesis that JCV is ubiquitous in the healthy human population, and not just diseased populations, which may have implications with JCV treatment, screening, and vaccine development. To the best of our knowledge, this is the first meta-analysis conducted on JCV seropositivity in healthy populations.